Induced antibiotic resistance and staphyloxanthin as a prospective target for treatment against pathogenic antibiotic-resistant staphylococci - Meyer, Jacobus Johannes Marion (University of Pretoria, 2023)
Dissertation (MSc (Medicinal Plant Sciences))--University of Pretoria, 2023.